2015
DOI: 10.1186/s12986-015-0036-z
|View full text |Cite
|
Sign up to set email alerts
|

High fat plus high cholesterol diet lead to hepatic steatosis in zebrafish larvae: a novel model for screening anti-hepatic steatosis drugs

Abstract: BackgroundNon-alcoholic fatty liver disease (NAFLD), characterized as excessive lipid accumulation within hepatocytes, is growing in prevalence. The exploitation of effective drugs for NAFLD has been proven challenging. Herein, we aimed to establish a dietary model of hepatic steatosis using transparent zebrafish larvae in which high-throughput chemical screens could be conducted.MethodsZebrafish larvae fed with high fat (HF) diet and high fat plus high cholesterol (HFC) diet were compared to the control. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 44 publications
1
63
0
Order By: Relevance
“…The zebrafish is an excellent model system for studying liver diseases because of the organ system homology to humans including cell types and gene expressions. 6,7 Zebrafish larvae have been used to study alcoholic and nonalcoholic fatty liver disease 6,[8][9][10] ; however, results from larvae may not represent chronic liver disease in adults. Adult zebrafish have not been used as a model for fatty liver disease, but recent articles reported fatty liver development after chronic alcohol exposure or trans-fat diet in adult zebrafish.…”
Section: Introductionmentioning
confidence: 99%
“…The zebrafish is an excellent model system for studying liver diseases because of the organ system homology to humans including cell types and gene expressions. 6,7 Zebrafish larvae have been used to study alcoholic and nonalcoholic fatty liver disease 6,[8][9][10] ; however, results from larvae may not represent chronic liver disease in adults. Adult zebrafish have not been used as a model for fatty liver disease, but recent articles reported fatty liver development after chronic alcohol exposure or trans-fat diet in adult zebrafish.…”
Section: Introductionmentioning
confidence: 99%
“…ER stress, which is known to incur steatosis, leads to disorder of lipid metabolism and induces lipid droplet deposition in zebrafish liver . Here, we observed that the expression levels of atf4 and chop were elevated in the zebrafish liver exposed to TCC compared with those in the control, indicating that TCC leads to ER dysfunction.…”
Section: Resultsmentioning
confidence: 66%
“…Heat shock protein 90 kDa alpha (cytosolic), class A member 1 (HSP90AA1) was the only gene that was significantly upregulated. Expression levels of endoplasmic reticulum molecule Heat shock protein 90 kDa beta (Grp94), member 1 (HSP90B1) were significantly up-regulated in the livers of zebrafish larvae fed high fat with or without high cholesterol diets [27]. Baculoviral IAP repeat containing 3 (BIRC3), a severe hypoxia-activated gene, was significantly increased in simple hepatic steatosis compared with the controls [28].…”
Section: Knockdown Of Arrdc3 Inhibits Inflammasome-associated Gene Exmentioning
confidence: 99%